2016
DOI: 10.4103/0976-237x.194114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Streptococcus mutans in healthy versus gingivitis and chronic periodontitis: A clinico-microbiological study

Abstract: Background:Dental caries and periodontal disease are most common oral diseases. Streptococcus mutans are considered to be the major pathogens in initiation of dental caries. Evidence shows that periodontal disease and caries share a number of contributory factors. Thus in view of these findings it would be worthwhile to examine whether Streptococcus mutans persist within the saliva and subgingival environment of the periodontitis patients and to determine whether there is any association between Streptococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 22 publications
2
43
0
1
Order By: Relevance
“…A higher presence of S. mutans ( Figure 1) in patients with chronic moderate or severe periodontitis before extraction of teeth might derive from a lower oxygen tension within the periodontal pockets [10]. This is in accordance to studies by Cortelli et al [11] and Dani et al [12] who found a high proportion of this microorganism in subgingival plaque samples of chronic periodontitis patients.…”
Section: Discussionsupporting
confidence: 87%
“…A higher presence of S. mutans ( Figure 1) in patients with chronic moderate or severe periodontitis before extraction of teeth might derive from a lower oxygen tension within the periodontal pockets [10]. This is in accordance to studies by Cortelli et al [11] and Dani et al [12] who found a high proportion of this microorganism in subgingival plaque samples of chronic periodontitis patients.…”
Section: Discussionsupporting
confidence: 87%
“…mutans is located in the subgingival biofilm collected from both patients with healthy gingival condition and with periodontal disease. However, the behavior of the bacteria, such as sucrose consumption, acid, and glycan production, was different (Dani et al, 2016). S .…”
Section: Introductionmentioning
confidence: 99%
“…(2012) discovered the presence of P. endodontalis is associated with chronic periodontitis. Dani et al (2016) found that S. mutans is considered to be one of the major pathogens in dental caries and is very likely to induce periodontal disease. A molecular survey by Griffen revealed new species Filifactor alocis is strongly associated with periodontal disease (Griffen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%